PREVALENCE OF DEPRESSION AND ITS ASSOCIATION WITH SOCIAL SUPPORT, AND TREATMENT ADHERENCE AMONG HIV-POSITIVE MEN WHO HAVE SEX WITH MEN AT OUTPATIENT CLINICS IN HO CHI MINH CITY (Vietnam Journal of Community Medicine, 2026)
1) Objectives: To determine the prevalence of depression and its associations with social support and treatment adherence among HIV-positive men who have sex with men (MSM) at outpatient clinics in Ho Chi Minh City.2) Methods: A cross-sectional study on 412 MSM patients receiving ARV treatment at three ward health stations: Xom Chieu, Cho Lon, and Phu Tho Hoa. Chi-square () and Fisher's exact tests were utilized to determine the relationships between independent variables and depression status.3) Results: The prevalence of depression was 16.3%. The treatment adherence rate was very high at 93.9%, and the majority of patients reported high (43.0%) and moderate (35.9%) levels of social support. The study found statistically significant associations between depression and both treatment adherence (p = 0.033) and the level of social support (p = 0.036). Additionally, income and sexual behavior characteristics were also related to depression (p < 0.05).4) Conclusions: In univariate analysis, depression in MSM was significantly correlated with social support and treatment adherence. It is necessary to strengthen social support networks and psychological interventions to optimize ARV treatment efficacy.
Keywords: Depression, Social support, MSM, Treatment adherence, HIV/AIDS.